Iris : a memoir of Iris Murdoch - Bayley, John, 1925-2015 (Duckworth, 1998)
At times unbearably moving, at times poignantly comical, this memoir provides a fitting memorial to Dame Iris. It is an enchanting portrait of a remarkable marriage and an inspiration for anyone whose life is affected by Alzheimer's.